Expression of rat renal Na/H antiporter mRNA levels in response to respiratory and metabolic acidosis. - Krapf, R (1991)
The mammalian proximal tubule is an important mediator of the renal adaptive response to systemic acidosis. In chronic metabolic and respiratory acidosis the bicarbonate reabsorptive (or proton secretory) capacity is increased. This increase is mediated, at least in part, by an increase in Vmax of the luminal Na/H antiporter. To determine whether this adaptation involves increased mRNA expression, Na/H antiporter mRNA levels were measured by Northern analysis in renal cortex of rats with metabolic (6 mmol/kg body wt NH4Cl for 2 or 5 d) and respiratory (10% CO2/air balanced for 2 or 5 d) acidosis and of normal, pair-fed rats. Na/H antiporter mRNA levels were unchanged after 2 d of both metabolic and respiratory acidosis. After 5 d, however, Na/H antiporter mRNA expression was increased 1.76 +/- 0.12-fold in response to metabolic acidosis (P less than 0.005, n = 8), but was not different from normal in response to respiratory acidosis: 1.1 +/- 0.2 (NS, n = 8). Thus, the renal adaptive response to metabolic acidosis involves increased cortical Na/H antiporter mRNA levels. In contrast, the enhanced proximal tubule Na/H antiporter activity and bicarbonate reabsorption in respiratory acidosis seem to involve mechanisms other than increased Na/H antiporter gene expression.